Desarda’s versus Lichtenstein technique of inguinal hernia repair: a comparative study - Akhtar, Mohammad Sadik; Mani, Suraj Kant; Alvi, Yasir; Alam, Parveg; Rizvi, Syed Amzad Ali; Raza, Mohammad Habib (International Surgery Journal, 2019)
Background: Inguinal hernias rank among the commonest of all hernias and surgery is the only definitive treatment. We analyzed the outcomes of desarda tissue based repair in comparison with the standard Lichtenstein tension free mesh repair of primary inguinal hernia. Methods: A total of 164 patients were randomly allocated into two groups, Desarda (group D) or Lichtenstein (group L) (80 VS 84, respectively). The primary outcome measures were chronic groin pain and recurrence during the follow up period. Secondary outcome measures included operating time, post-operative pain scores, duration of post-operative hospital stay, time to return to basic physical activity and to work, foreign body sensation, and post-operative complications. Results: During two year follow up, no recurrence was detected in each group. Operative time was significantly less in the Desarda group (28.91±5.82 min as compared to 34.07±8.63 min in the Lichtenstein group). Postoperative day 1, day 3 and day 7 groin pain was more in the Desarda as compared to the Lichtenstein group. Basic physical activity, chronic groin pain, cost, seroma formation, foreign body sensation, were also significantly less in the Desarda group. Conclusions: The successful primary inguinal hernia repair without mesh implantation can be achieved using Desarda tissue based repair, as it is effective as the standard Lichtenstein tension free mesh repair. Shorter operative time, early return to basic physical activity, lower cost, less chronic groin pain, less foreign body sensation are potential benefits of Desarda repair and can be preferred for inguinal hernia repair.